Mobilizable Plasmids for Tunable Gene Expression in Francisella novicida - Brodmann, Maj; Heilig, Rosalie; Broz, Petr; Basler, Marek (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis is the causative agent of the life-threatening disease tularemia. However, the molecular tools to study Francisella are limited. Especially, expression plasmids are sparse and difficult to use, as they are unstable and prone to spontaneous loss. Most Francisella expression plasmids lack inducible promoters making it difficult to control gene expression levels. In addition, available expression plasmids are mainly designed for F. tularensis, however, genetic differences including restriction-modification systems impede the use of these plasmids in F. novicida, which is often used as a model organism to study Francisella pathogenesis. Here we report construction and characterization of two mobilizable plasmids (pFNMB1 and pFNMB2) designed for regulated gene expression in F. novicida. pFNMB plasmids contain a tetracycline inducible promoter to control gene expression levels and oriT for RP4 mediated mobilization. We show that both plasmids are stably maintained in bacteria for more than 40 generations over 4 days of culturing in the absence of selection against plasmid loss. Expression levels are dependent on anhydrotetracycline concentration and homogeneous in a bacterial population. pFNMB1 and pFNMB2 plasmids differ in the sequence between promoter and translation start site and thus allow to reach different maximum levels of protein expression. We used pFNMB1 and pFNMB2 for complementation of Francisella Pathogenicity Island mutants ΔiglF, ΔiglI, and ΔiglC in-vitro and pFNMB1 to complement ΔiglI mutant in bone marrow derived macrophages.